First assessment of the health status of pregnant women, detection of prevalence and risk factors associated with enzootic ovine abortion disease among pregnant women in southern Benin - Kifouly, Aboudou Habirou; Bekindaka, Ngemani Obase; Ali, Kaltun Said; Rume, Juliana; Okunlola, Michael (Frontiers in Public Health, 2025)
IntroductionThis study aims to access for the first time in the Benin Republic, the characteristics of the health status and the serological prevalence of Chlamydia abortus in pregnant women. Enzootic Abortion of Ewes (EAE) is a bacterial illness that can harm sheep by producing abortions and miscarriages in pregnant women.MethodsAbout six municipalities under two governorates were concerned and around 420 pregnant women were enrolled for the survey (210 participants in each governorate). Among of this enrollment, 385 participants were concerned for serological test.ResultsOur result showed that this survey among pregnant women at the Sakété-Ifangni health zone hospital revealed that 125 participants (59.52%) had been exposed to potentially infected animals or products, with 40% having touched items from sick animals. Overall, 65.24% of animal owners were unsure whether they had been exposed. As much as 28 to 38% of the women farmed alongside their husbands, which frequently led to direct contact with aborted products. The consumption of milk from small ruminants was 26.67%. This consumption was associated with the risk of Chlamydia abortus. Half of them had experienced pregnancy complications. Knowledge of Chlamydia abortus varied from 16 to 68.5%. Proximity to small ruminant farms increases the risk of infection. Awareness among healthcare professionals needs to be improved. Although, the serological prevalence observed was relatively low (1.30%), it reveals a significant past exposure to the pathogen, especially in rural or cross-border areas such as the majority of the municipalities involved in this study.ConclusionThis data constitutes an epidemiology alert, justifying the introduction of additional methods such as PCR to access the active circulation and refine prevention strategies.